Growth and properties of polar and non-polar InGaN/GaN LEDS on patterned and M-plane sapphire substrates / Mohd Adreen Shah Azman Shah - Mohd Adreen Shah , Azman Shah (2022)
In this study, metal-organic chemical vapour deposition (MOCVD) was employed to assist in the growth of polar c-plane (0001) and non-polar m-plane (10-10) GaNs on the c-plane cone-patterned sapphire substrate (CPSS) and the m-plane sapphire substrate, respectively. There are two main sections in each chapter, namely Section A for the growth of polar (0001) gallium nitride (GaN) and Section B for the growth of non-polar (10-10) GaN. The work in each section involved an optimisation towards the light-emitting diode’s (LED) structure. The structure consisted of the unintentionally (uid) doped GaN, the n-type GaN, indium gallium nitride/gallium nitride (InGaN/GaN) multi-quantum wells (MQWs), InGaN/GaN strained layer-superlattices (SLS) and the p-type GaN. Remarkably, both planes featured different epitaxial growth techniques to produce good crystal quality for the enhanced performance of the device. The implementation of the three-step approach was found to solve the agonising issue related to the crystal quality deterioration of m-plane GaN. A comparative study between these two planes revealed that the non-polar growth was sensitive towards the parameter’s variations in the MOCVD reactor, while the polar growth was likely stable in terms of molar ratio (V/III), pressure and growth temperature. This, in turn, led to the superior crystal quality of the polar plane compared with the non-polar plane. The epilayer properties of both planes were studied with special emphasis on the role of nucleation layer, buffer layer, recrystallisation, and growth condition towards the effect on threading dislocations and basal stacking faults. The electrical properties for both planes achieve the targeted carrier concentration as well as the mobility by optimising the disilane (Si2H6) and bis-cyclopentadienyl magnesium (Cp2Mg) flow rate for the growth of n-type and p-type. The growth of InGaN/GaN MQW starts with the optimisation by varying the molar ratio from group III of trimethylindium to triethylgallium. Each series of mol ratio is grown at different MQW growth temperature to understand the relation between temperature and emission wavelength of the active region. The insertion of InGaN/GaN SLS at 20 pairs helps to enhance the performance of polar and non-polar LEDs. As a result, the output power of c-plane InGaN/GaN blue LEDs is improved by 61.1% at an injection current of 20 mA after implementing the embedded InGaN/GaN SLS layer. The m-plane InGaN/GaN cyan LED with 20 pairs of SLS exhibit an output power of 0.39 mW at an injection current of 20 mA. A high-resolution X-ray diffraction (HR-XRD) technique including phase analysis (PA) , X-ray rocking curve (XRC) and reciprocal space mapping (RSM) is tested on both planes. The surface morphology analysis was investigated by atomic force microscopy (AFM) and field-emission scanning electron microscopy (FESEM). The secondary ion mass spectroscopy (SIMS) profiles revealed the content of Si- and Mg-atomic fraction as well as the depth of SLS. The concentrations of Ga and In atoms in the MQW were defined as atomic fraction and the ~11% of indium atomic fraction was obtained for the polar plane and ~33% for the non-polar plane. The electrical properties were analysed by Hall effect measurements and electroluminescence (EL) spectrum analysis. This work shall be a good framework for the comparison of the growth window’s parameters and the performances of polar c- and non-polar m-plane GaN LEDs.